Examining the behavior changes in belief and attitude among smart phone users for mobile learning - Yong, Wee Sek; Siong, Hoe Lau; Hasan Basari, Abd Samad; Hussin, Burairah (2010)
Prior empirical studies have articulated that IT adoption and usage were determined by user beliefs and attitudes toward IT. We adopted Technology Acceptance Model’s constructs to conduct a case study across two stages; Introduction and hand-on to examine the changes in users’ beliefs and behavioral intention to use smart phone for learning. This paper reports on a study of 60 potential users on smart phones. The results show that the hand-on session was effective in improving users’ beliefs and intentions to use smart phones for learning.